Studi Keberadaan Cemaran Formalin dan Timbal (Pb) pada Tahu yang Dijual Pedagang Gorengan Tahu Petis di Sekitar Kampus Universitas Diponegoro - Dian Dwi Restiani; Dwi Sutiningsih; Retno Hestiningsih (Master of Epidemiology, School of Postgraduate Studies, Diponegoro University, Indonesia, 2020)
Background: Tahu Petis is one of the street foods that are prone to Pb contamination from motor vehicle emissions and formaldehyde from tofu. Minister of Health Regulation No. 33 of 2012 prohibits formalin as a food additive and the National Agency for Drug and Food Control regulates the maximum limit of lead contamination in food which is 0.2 mg/kg. Formalin and lead are dangerous if they enter the human body because they can cause cancer and decrease intelligenceMethods: This research method used an analytic survey method with a cross-sectional approach. Data collected through interviews, observations, and laboratory examinations. The number of samples in this study was 30 fried tofu from 30 traders.Result: The results showed that 46.7% of samples were positive formalin with a range of 2.25-13.25 ppm and 40% of samples were positive Pb with a range of levels of 0.29-11.53 ppm. The knowledge factor (p=0.153), tofu processing (p=0.157), and tofu storage (p=0.464) did not have a significant relationship with the presence of formalin in the sample. Knowledge factor about Pb (p=0.049) showed a significant relationship with the presence of Pb in the sample, while the use of cooking oil (p=0.266) the distance factor of exposure (p=0.547), length of exposure (p=0.660), and presentation of Tahu Petis (p=1) did not show a significant relationship.Conclusion: Based on these results, it is recommended that there be periodic examinations guidance, and supervision of formaldehyde and Pb contamination in food.